Promoting the rights of elderly with disabilities through the UN convention on the rights of Persons with disabilities: lesson for Malaysia - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (2015)
The promotion and protection of the rights of persons with disabilities (PWD) have not seen much progress in the past decades. Disabled people especially the elderly have been mainly neglected. They need proper attention because they are weak,handicapped, and unable to live and make decision independently. The United Nations Convention of the Rights of Persons with Disabilities (CRPD) has provided significant attention to the elderly with disabilities to improve their rights especially relating to their life, dignity, employment, social security, health and housing. Under the convention State Party must include protection and care for elder with disabilities within its legal and policy framework. As a State Member to CRPD, Malaysia has enacted the Persons with Disabilities Act 2008 to fulfil the international obligations improving the laws and policy relating to disabled people. Malaysia has two policies related with elderly; National Policy for the Elderly and National Health Policy for Older Persons. These policies however, focus disability in terms of access to health rather than other rights that might suit with elderly with disabilities. With the existence of CRPD and PWD Act 2008, there is needed to consider broader rights of elderly with disabilities including social support system, accessible rights to buildings, facilities, employment, education and situation of risks and humanitarian emergencies. Thus, it is pertinent to analyse the possible legal and policy strategies that can be implemented in Malaysia to provide such protection for elderly with disabilities from being abused and neglected by the society.